A model for collaboration between allopathic and traditional health practitioners in the management of HIV/AIDS and TB patients in Vhembe District, Limpopo Province - Hendricks, S.J.H. (Stephen) (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2016.